Pragmatism, feminism, and democracy : rethinking the politics of American history - Livingston, James, 1949- (Routledge, 2001)
Pragmatism, Feminism, and Democracy is James Livingston's virtuoso reflection on the period between 1890 and 1930, a primal scene of American history during which a wave of intellectual currents came together--and fell apart--to reorient society. Tying in critical insights on corporate capitalism, consumer culture, populism, and the American Left, Livingston analyzes the intersections and similarities of pragmatism and feminism to yield an original, provocative blend of historiography, feminist theory, and American intellectual history.